Don Dimas de La Tijereta and the scribe job in Lima Historical clarifications based on a Lima tradition - Chuhue Huamán, Richard (2021)
Dimas de la Tijereta is one of the most well-known and widespread traditions bequeathed to us by Ricardo Palma Soriano (1833 - 1919). In this story the main character is referred to as the president of the guild of scribes of Lima, an entity that existed in real life and about which we will detail aspects in the following lines. Likewise, we will present characteristics and singularities about the scribe job in colonial Peru. With this article, we also want to specify some of the historical data of this tradition, since although it is true Ricardo Palma is a writer who recreates situations of the Peruvian past through his prose, they deserve to be understood in their real context and detail.